SMBs in Poland from the evolutionary economics perspective (Economic and Political Thought, 2015)
The article discusses the issue of development of small and medium-sizedbusinesses in Poland from the perspective of evolutionary economics. Theevolution of the SMBs sector and the development of its present shape inPoland started in the 1980s. At the same time (in the early 80s), evolutionaryeconomics placed hopes on the creation of alternative theory in relation tothe neoclassical approach. Eventually, the sector went through various stagesof evolution, which authors defined and specified differently. Diversity wasnothing bad in this area, just the opposite – it made it possible to work outmany mutually supplementing theses and views on the issue from a broadperspective. However, in the author’s opinion, it is necessary to take intoaccount the sixth stage of the sector’s evolution (five stages are usually discussedin literature), which would reflect the development state of the sector’spopulation after the completed process of assistance of the European Union.